2019
DOI: 10.1038/s41598-019-43567-y
|View full text |Cite
|
Sign up to set email alerts
|

Integration of bilateral nociceptive inputs tunes spinal and cerebral responses

Abstract: Together with the nociceptive system, pain protects the body from tissue damage. For instance, when the RIII-reflex is evoked by sural nerve stimulation, nociceptive inputs activate flexor muscles and inhibit extensor muscles of the affected lower limb while producing the opposite effects on the contralateral muscles. But how do the spinal cord and brain integrate concurrent sensorimotor information originating from both limbs? This is critical for evoking coordinated responses to nociceptive stimuli, but has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 81 publications
4
19
1
Order By: Relevance
“…The results show that bilateral stimulation leads to a greater increase in pain perception when the hands are in the near compared with the far position, consistent with the effect on the P2 and previous studies (Lautenbacher et al, 2007;Quevedo & Coghill, 2007). The results may also explain why bilateral noxious stimuli increased pain when applied on both feet (close from each other), but not on both hands (70 cm apart) or on a foot and a hand (Northon et al, 2019(Northon et al, , 2021a(Northon et al, , 2021bRustamov et al, 2019). Although this should be examined in future studies, it could be speculated that this effect is related to perceptual fusion and to the overlap in the limb-centered peripersonal space of each limb .…”
Section: Effects Of Limb Position On the Interaction Of Bilateral Noxious Inputssupporting
confidence: 90%
See 4 more Smart Citations
“…The results show that bilateral stimulation leads to a greater increase in pain perception when the hands are in the near compared with the far position, consistent with the effect on the P2 and previous studies (Lautenbacher et al, 2007;Quevedo & Coghill, 2007). The results may also explain why bilateral noxious stimuli increased pain when applied on both feet (close from each other), but not on both hands (70 cm apart) or on a foot and a hand (Northon et al, 2019(Northon et al, , 2021a(Northon et al, , 2021bRustamov et al, 2019). Although this should be examined in future studies, it could be speculated that this effect is related to perceptual fusion and to the overlap in the limb-centered peripersonal space of each limb .…”
Section: Effects Of Limb Position On the Interaction Of Bilateral Noxious Inputssupporting
confidence: 90%
“…In previous studies, it was shown that spatial attention can modulate pain-related brain responses, especially when the features of the concurrent stimulus are distinct from the attended stimulus (Van Ryckeghem et al, 2013;Torta et al, 2017). In contrast, it was shown that attending and rating the right or left noxious stimulus during bilateral stimulation does not modulate pain-related brain responses (Blöchl et al, 2015;Northon et al, 2019;Rustamov et al, 2019). In the present study, instructions for pain ratings were adapted from previous studies on the spatial integration of pain (Lautenbacher et al, 2007;Nielsen & Arendt-Nielsen, 1997b;Quevedo & Coghill, 2007.…”
Section: Effects Of Spatial Attention On the Interaction Of Bilateral Noxious Inputsmentioning
confidence: 81%
See 3 more Smart Citations